Identification and Analysis of the Plasma Membrane H+-ATPase Gene Family in Cotton and Its Roles in Response to Salt Stress - Cong Cheng; Fengyuan Zhang; Li Li; Zhiyong Ni (Plants)
Plant plasma membrane (PM) H+-ATPase functions as a proton-motive force by exporting cellular protons to establish a transmembrane chemical gradient of H+ ions and an accompanying electrical gradient. These gradients are crucial for plant growth and development and for plant responses to abiotic and biotic stresses. In this study, a comprehensive identification of the PM H+-ATPase gene family was conducted across four cotton species. Specifically, 14 genes were identified in the diploid species Gossypium arboreum and Gossypium raimondii, whereas 39 and 43 genes were identified in the tetraploid species Gossypium hirsutum and Gossypium barbadense, respectively. The characteristics of this gene family were subsequently compared and analyzed using bioinformatics. Chromosomal localization and collinearity analyses elucidated the distribution characteristics of this gene family within the cotton genomes. Gene structure and phylogenetic analyses demonstrated the conservation of this family across cotton species, whereas the examination of cis-acting elements in gene promoters highlighted their involvement in environmental stress and hormone response categories. An expression profile analysis revealed eight genes whose expression was upregulated under salt stress conditions, and quantitative real-time PCR results suggested that the cotton PM H+-ATPase genes may play crucial roles in conferring resistance to salt stress. These findings establish a robust foundation for subsequent investigations into the functions of cotton PM H+-ATPase genes and may offer valuable insights for selecting genes for resistance breeding programs.